Coral Reefs: Beyond Mortality?. (2000) - Sheppard Sheppard, Charles Charles
Abstract : The scale of the collapse of coral reef communities in 1998 following a warming episode (Wilkinson, 2000) was unprecedented, and took many people by surprise. The Indian Ocean was the worst affected with a coral mortality over 75% in many areas such as the Chagos Archipelago (Sheppard, 1999), Seychelles (Spencer et al., 2000) and Maldives (McClanahan, 2000). Several other locations were affected at least as much, with mortality reaching 100% (to the nearest whole number); this is being compiled by various authors (e.g., CORDIO, in press). For example, in the Arabian Gulf, coral mortality is almost total across many large areas of shallow water (Sheppard, unpublished; D. George and D. John, personal communication). The mortality is patchy of course, depending on currents, location inside or outside lagoons, etc., but it is now possible to swim for over 200 m and see not one remaining living coral or soft coral on some previously rich reefs.